Students’ Power Relationships within an EFL Classroom - Gutiérrez Pulido, Lila Maribel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper reports the results of a research study whose main purpose was to identify aspects related to power relationships in a group of ninth-grade English learners. An EFL classroom was used as the setting to analyze power relationships among students. A qualitative case study was carried out in a public school from Sogamoso; the participants were 8 students, selected at random from a group of 35. The data was gathered through field notes, video recordings and focused interviews. After analyzing the data, it was found that aspects connected to power relationships sometimes either helped or hindered the participants’ English language learning process. Positive and negative features concerning power relationships within the EFL classroom were identified. Positive features include the use of power to motivate the accomplishment of tasks.  Negative features include the use of power to suppress others thereby limiting their ability to express opinions in class.